Feeding cues: a concept analysis - Dewi Irianti; Dessie Wanda; Fajar Tri Waluyanti; Mega Hasanul Huda (Universitas Airlangga, 2026)
Introduction: Premature infants often experience delays in developing oral feeding skills essential for their growth. This may be due to immature motor development and physiological instability. Inconsistent definitions of feeding cues can also affect the quality of care provided. Therefore, a concept analysis of feeding cues in premature infants is necessary to clarify definition and improve the accuracy of care to meet their needs. This study aimed to clarify the concept of feeding cues in premature infants.Methods: The Walker and Avant concept analysis method was used. A literature search was also conducted from five databases: PubMed, ProQuest, ScienceDirect, Scopus, and Google Scholar for 2000 and later.Results: The literature search obtained 20 articles on feeding cues from various disciplines. Eight attributes were developed from the concept analysis, including (1) behavioral and physiological signs, (2) readiness to feed, (3) transition and awareness ability, (4) hand and mouth movements, (5) effective sucking and swallowing, (6) self-regulation, (7) behavioural changes, and (8) facial expression. Antecedents to feeding cues include infant physiology, infant’s level of consciousness changes, infant motor and reflex development, respiratory stability and health status, and availability of feeding resources. Consequences include timely and appropriate feeding according to infant’s needs, infant’s self-regulation, infant’s comfort and stability, development of a positive caregiver-infant relationship, and balance of energy intake and growths.Conclusion: The concept analysis provides eight comprehensive attributes and their antecedents and consequences, emphasising the importance of understanding feeding cues in premature infants. This understanding can guide nursing care, enhance early feeding interventions, and support the growth and development of premature infants to enhance the quality of nursing care in this group.Keywords: concept analysis; feeding cues; premature infants